ADAPTASI STRUKTUR ORGANISASI SEBAGAI STRATEGI KEBERLANJUTAN EKSISTENSI PESANTREN - Taufiqurrahman, Taufiqurrahman (Fakultas Tarbiyah, Universitas Ibrahimy, 2018)
Islamic boarding school is indigenous educational institution of Indonesia. It began since ‘wali songo’ era, preciously Sunan Ampel. The oldest Islamic boarding school which exists is SidogiriIslamic boarding school (est. 1745). Islamic boarding school contributes massively in struggling to, defending of and developing the independence. This fact is evidenced by conferment of National patriot for founder of islamic boarding school, such as KH. Hasyim Asy’ari and KHR.As’ad Syamsul Arifin. Islamic boarding school as an organisasion is success to maintain their existence for long-term sustainability. The critical factor for their success is an ability to adapt the organizational structure to their internal- and external-environment. Islamic boarding school as organization is unique, different from corporate, and sub-culture of Indonesian sociocultural system. Hypotheses of successful of islamic boarding school are firstly, integrity of kyai, which is supported by clear ukhrawi vision; secondly, openness to development of knowledge and technology, while firstly considering respectable books of turath, and thirdly, kiai and santri’s socio-cultural and intellectual model which will be interchanged in the field.